RECONSTRUCTION OF LEGAL PROTECTION FOR TEACHERS IN CONDUCTING EDUCATION IN INDONESIA - Budi Siswani, Carina (International Journal of Law Social Sciences and Management, 2024)
This research aims to analyze and reconstruct the legal protection for teachers in conducting education in Indonesia. The dynamic changes in the education system pose new challenges and complexities that affect the roles of teachers in shaping the future generation. The research findings indicate that despite the existence of several laws regulating legal protection for teachers, their implementation still faces constraints and obstacles. Therefore, a reconstruction within the legal framework is needed to ensure more effective and comprehensive protection for teachers. This reconstruction involves refining legislation, enhancing law enforcement mechanisms, and strengthening the roles of relevant institutions. Additionally, the research highlights the importance of showing greater appreciation for the role of teachers in educating and shaping the character of students. Thus, the reconstruction of legal protection for teachers is not only an effort to safeguard their rights but also a recognition of their contributions to creating a quality society through education.